Realization of principle of textocentrism in the process of forming of communicative skills and habits (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article is devoted to a problem of communicative skills and habits formation  of the pupils on the basis of the text. The author proved the necessity of  realization of textocentrism principle in the process of  teaching of Ukrainian language, the didactical possibilities of text for developing the pupils’ speech, the analysis of text as an effective way for forming skills and habits of speech is also characterized in the article.
Keywords: communicative-functional way; textocentrism principle; text; communicative skills and habits